Deactivation blocks proton pathways in the mitochondrial complex I - Röpke, Michael (Proc Natl Acad Sci U S A, 2021)
Cellular respiration is powered by membrane-bound redox enzymes that convert chemical energy into an electrochemical proton gradient and drive the energy metabolism. By combining large-scale classical and quantum mechanical simulations with cryo-electron microscopy data, we resolve here molecular details of conformational changes linked to proton pumping in the mammalian complex I. Our data suggest that complex I deactivation blocks water-mediated proton transfer between a membrane-bound quinone site and proton-pumping modules, decoupling the energy-transduction machinery. We identify a putative gating region at the interface between membrane domain subunits ND1 and ND3/ND4L/ND6 that modulates the proton transfer by conformational changes in transmembrane helices and bulky residues. The region is perturbed by mutations linked to human mitochondrial disorders and is suggested to also undergo conformational changes during catalysis of simpler complex I variants that lack the “active”-to-“deactive” transition. Our findings suggest that conformational changes in transmembrane helices modulate the proton transfer dynamics by wetting/dewetting transitions and provide important functional insight into the mammalian respiratory complex I.